Application of 4A Concept in Bogor Botanical Garden Tourism Development Strategy - Yohana, Yohana; Nugraha, Rizki Nurul (Westscience Press, 2024)
Indonesia is very rich in natural tourism potential (ecotourism), one of which is natural tourism in conservation areas. Bogor Botanical Garden is an ex-situ conservation area that has long been used by the wider community as a tourist attraction and in many countries, Bogor Botanical Garden is one of the most popular tourist destinations because it presents a panoramic view of natural landscape architecture. The research entitled